Isolamento e resistência a antimicrobianos de cepas de Streptococcus spp. provenientes de rãs-touro (Lithobates catesbeianus) - Pilarski, F. [UNESP]; Schocken-Iturrino, R. P. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2010)
Twelve bullfrogs were selected from two commercial frog farms and clinically diagnosed as attacked by Streptococcus disease. Sixty samples were collected, and Streptococcus spp. was isolated from all bullfrog, being 12 (100%) from the encephalus, seven from the kidneys (58.3%), three from the liver (25%), two from the spleen (16.6%), and one from the ascitic liquid (8.3%). Streptococcus -hemolytic were isolated from all the 60 samples, which were sensible to chloramphenicol (100%), gentamycin (100%), vancomycin (96%), cefotaxime (96%), and cefoxitine (92%).
Isolation and antimicrobial resistance of Streptococcus spp. strains from bullfrog (Lithobates catesbeiana)